Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens